2020
DOI: 10.21037/jtd-20-2666
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous implantation of 125I particles in treatment of early lung cancer

Abstract: Background:To analyze the efficacy of computed tomography (CT)-guided implantation of 125 I radioactive particles in treatment of early lung cancer. Methods: Six patients were analyzed, including 4 squamous cell carcinoma, 1 adenocarcinoma, and 1 small cell lung cancer. TPS software was used to calculate the therapeutic dose amount of particles implanted, and the spacing and distribution of seeds in the target area and adjacent tissues. Under the guidance of CT, 20-55 particles were implanted at each site, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this study, a left-sided cervical anastomosis was combined with a ^(125)I particle-loaded nutrition tube. This treatment combines nutritional support and chemotherapy treatment, with (125)I particles applied to the tube and covered by the tube, allowing the particles to radiate close to the original tumor lesion, effectively removing residual tumor cells around the original tumor lesion and further enhancing its overall anti-tumor therapeutic efficacy ( 11 ). In order to investigate the therapeutic effect of left-sided cervical anastomosis combined with ^(125)I particles in esophageal cancer, this study compared the IGFBP-2 expression level and nutritional status before and after treatment of esophageal cancer and in healthy physical examination patients at the same period.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a left-sided cervical anastomosis was combined with a ^(125)I particle-loaded nutrition tube. This treatment combines nutritional support and chemotherapy treatment, with (125)I particles applied to the tube and covered by the tube, allowing the particles to radiate close to the original tumor lesion, effectively removing residual tumor cells around the original tumor lesion and further enhancing its overall anti-tumor therapeutic efficacy ( 11 ). In order to investigate the therapeutic effect of left-sided cervical anastomosis combined with ^(125)I particles in esophageal cancer, this study compared the IGFBP-2 expression level and nutritional status before and after treatment of esophageal cancer and in healthy physical examination patients at the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-125 seed implantation therapy was first used in the treatment of prostate cancer, and with the continuous innovation and improvement of medical technology, it is now widely used in treating various malignancies. Its' efficacy has been fully verified in the treatment of NSCLC [10][11][12]. A meta-study on NSCLC showed significant differences in ORR, disease control rate (DCR), and OS between 125 I brachytherapy in combination with chemotherapy and chemotherapy alone, confirming the clinical benefit of 125 I seed implantation for NSCLC treatment [14].…”
Section: Discussionmentioning
confidence: 89%
“…Iodine-125 ( 125 I) radioactive seed implantation therapy is a local treatment that has been widely used in treatment of various malignancies [7][8][9]. With the advantages of low doses, small adverse reactions, and minimal invasiveness, it has been increasingly applied in treating NSCLC, achieving certain efficacy [10][11][12]. However, this method is rarely used in SCLC treatment.…”
Section: Purposementioning
confidence: 99%
“…5 Computational and Mathematical Methods in Medicine of CT imaging big data-assisted arterial chemoembolization combined with 125 I seed implantation for NSCLC was higher than arterial chemoembolization alone, without significantly increasing the incidence of adverse reactions, suggesting that the combination treatment can effectively inhibit NSCLC progression. The reason for the results may be that 125 I radioactive seeds are a kind of long half-life particles and can emit continuously low energy gamma rays, which can enhance the self-sensitization of the tumor cells and improve the sensitivity and killability of cancer cells, thus greatly improving treatment effect [19,20].…”
Section: Discussionmentioning
confidence: 99%